IL-2 and IL-4 Serum Levels in Breast Cancer - Al-Ghurabi, Batool H. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: The role of cytokines in cancer immunity and carcinogenesis in general has been well established, which play an important role in the pathogenesis of many solid cancers.This study aimed to estimate serum levels of IL-2 and IL-4, and to shed light on the correlation of these interleukins with progression of breast cancer.Patients and Methods: The study included 80 women, it comprised of 45 breast cancer patients, 12 patients with benign breast lesions and 23 apparently healthy controls. ELISA method has been used for estimation the level of IL-2 and IL-4 in serum of three studied groups.Results: This study showed elevation of IL-4 level in the sera of breast cancer patients with significant differences between breast cancer and controls (p